2022
DOI: 10.1002/cb.2106
|View full text |Cite
|
Sign up to set email alerts
|

Relating social skills and social media use to consumer behavior: An investigation across the autism spectrum

Abstract: In this study, we focus on the role of social functioning on consumer behavior, exploring social media use as a mediating factor. In order to facilitate our identification of social functioning competence as a factor, we increased the range by including a subgroup of respondents who identified themselves as being on the autism spectrum. Indeed, this group stood out as having difficulties in getting along with persons they interact with at school, at work and at home. We used these measures to define an individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Studies in children with Costello syndrome [ 100 ], a disease that results in malformations of cortical development, and 22q11.2 deletion syndrome [ 101 ], which is also associated with developmental delay, have also found increased spindling activity. On the other hand, most other studies have found reduced or even largely absent spindle activity in a wide variety of developmental disorders including cerebral palsy [ 102 104 ], late infantile neuronal ceroid [ 105 ] lipofuscinosis (LINCL), 15q11.2–13.1 [ 106 ], and Angelman syndrome [ 107 ]. Taken together, it is likely that different disorders (or even within a disorders class) impact the thalamocortical system in a variety of ways and give rise to a range of spindle features.…”
Section: Sleep Spindles In Neurodevelopmental Disordersmentioning
confidence: 99%
“…Studies in children with Costello syndrome [ 100 ], a disease that results in malformations of cortical development, and 22q11.2 deletion syndrome [ 101 ], which is also associated with developmental delay, have also found increased spindling activity. On the other hand, most other studies have found reduced or even largely absent spindle activity in a wide variety of developmental disorders including cerebral palsy [ 102 104 ], late infantile neuronal ceroid [ 105 ] lipofuscinosis (LINCL), 15q11.2–13.1 [ 106 ], and Angelman syndrome [ 107 ]. Taken together, it is likely that different disorders (or even within a disorders class) impact the thalamocortical system in a variety of ways and give rise to a range of spindle features.…”
Section: Sleep Spindles In Neurodevelopmental Disordersmentioning
confidence: 99%
“…Consumer theory states that new services or products provided by entrants can be complementary or substitutes for existing companies. Emerging companies (such as P2P platforms) can be complementary to incumbents when new products provided by entrants can be used in conjunction with existing products to meet specific needs (Aaker & Keller, 1990;Levin & Milgrom, 2004). On the contrary, products provided by entrant companies become substitutes for existing companies when customers perceive the new products from the entrants as being able to replace existing products (Aaker & Keller, 1990;Phan et al, 2019).…”
Section: Disruptive Innovation Theory and Consumer Theorymentioning
confidence: 99%
“…On the other hand, research from Kohardinata et al (2020b) showed a shift in the influence of P2P lending on rural bank credit growth, from a negative effect (substitution) to a positive effect (complement). can be used together with previous products (Aaker & Keller, 1990;Levin & Milgrom, 2004); on the other hand, new services or products from entrant companies can be substitutes if they can replace old products (Aaker & Keller, 1990;Phan et al, 2019). This study needs to be carried out because the disruptive effect occurs if P2P lending disrupts the main banking market, namely the working capital credit market (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the course of time, a shift in the sequence of acquisition, use, and disposal are not out of the question. [8] European Economic Letters ISSN 2323-5233 Vol 13, Issue 5 (2023) https://doi.org/10.52783/eel.v13i5.1075 http://eelet.org.uk…”
Section: Characteristics Of Consumer Behaviormentioning
confidence: 99%